Vincristine Sulfate Liposomes Injection (VSLI, Marqibo®): Results From a Phase I Study in Children, Adolescents, and Young Adults With Refractory Solid Tumors or Leukemias - Shah, Nirali N.; Merchant, Melinda S.; Cole, Diane E.; Jayaprakash, Nalini; Bernstein, Donna; Delbrook, Cindy; Richards, Kelly; Widemann, Brigitte C.; Wayne, Alan S. (Pediatric blood & cancer, 2016)
Background Vincristine sulfate liposome injection (VSLI; Marqibo®) is an encapsulated preparation of standard vincristine in sphingomyelin/cholesterol liposomes. Clinical trials in adults have demonstrated safety, tolerability, and activity, leading to Food and Drug Administration (FDA) approval for adults with relapsed acute lymphoblastic leukemia (ALL). Pediatric experience with VSLI is limited. Procedure This single center, phase I dose escalation study examined the safety, toxicity, maximum tolerated dose, and pharmacokinetics of VSLI administered weekly to pediatric patients age <21 years with relapsed or chemotherapy‐refractory solid tumors or leukemia. Results Twenty‐one subjects were treated in total. Median age was 13.3 years (range 2–19). Fourteen subjects completed one 28‐day cycle of therapy and five subjects completed more than one cycle. No subject experienced dose‐limiting toxicity (DLT) at the first dose level (1.75 mg/m2/dose, dose range: 2–3.7 mg). At the second dose level (2.25 mg/m2/dose, dose range: 1.3–4.5 mg), one subject had transient dose‐limiting grade 4 transaminase elevation, and this dose level was expanded with no additional DLT observed. The second dose level then opened to an expansion phase to evaluate activity in ALL. Clinical activity included minimal residual disease negative complete remission in one subject with ALL and stable disease in nine subjects. Clearance of total vincristine was found to be approximately 100‐fold lower in comparison to published data using standard vincristine. Conclusions Children tolerate 2.25 mg/m2/dose of weekly VSLI (the adult FDA‐approved dose) with evidence for clinical activity without dose‐limiting neurotoxicity. Future plans include studying VSLI as substitution for standard vincristine with combination chemotherapy in children with ALL.